Acoustic Radiation Force Impulse Elastography for Efficacy Evaluation after Hepatocellular Carcinoma Radiofrequency Ablation: A Comparative Study with Contrast-Enhanced Ultrasound. (6th May 2014) - Xu, Xiaohong; Luo, Liangping; Chen, Jiexin; Wang, Jiexin; Zhou, Honglian; Li, Mingyi; Jin, Zhanqiang; Chen, Nianping; Miao, Huilai; Lin, Manzhou; Dai, Wei; Ahuja, Anil T.; et al.
Abstract : Aim . To explore acoustic radiation force impulse (ARFI) elastography in assessing residual tumors of hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA). Materials and Methods . There were 83 HCC lesions among 72 patients. All patients were examined with ARFI, contrast enhanced ultrasound (CEUS), and CT or MRI. Tumor brightness on virtual touch tissue imaging (VTI) and shear wave velocity (SWV) were assessed before and approximately one month after RFA. Results . There were 14 residual tumors after RFA. VTI showed that all the tumors were darker after RFA. VTI was not able to distinguish the ablated lesions and the residual tumors. 13 residual tumor lesions were detected by CEUS. All completely ablated nodules had SWV demonstration of x.xx., while with those residual nodules, 6 tumors had x.xx measurement and 8 tumors had measurable SWV. nine lesions with residual tumors occurred in cirrhosis subjects and 5 lesions with residual tumors occurred in fibrosis subjects; there was no residual tumor in the normal liver subjects. Conclusion . VTI technique cannot demonstrate residual tumor post RFA. While SWV measurement of less than x.xx is likely associated with residual tumors, measurement of less than x.xx cannot exclude residual tumors. Liver cirrhosis is associated with decreased chance of a complete ablation.